A diffuse scattering model for urban propagation prediction. - Degli-Esposti, V. (IEEE Transactions on antennas and propagation)
A novel, simple diffuse scattering model based on a ray approach suitable for urban radio propagation is presented. The scattering model is arranged so that the main parameters, having a precise physical meaning, can be easily tuned using measurement results. The model is tested against 900-MHz measurements and the scattering contribution is shown to be important for both received power and channel dispersion in a typical microcellular case